Not too Complicated

Algebra Level 4

Let f ( x ) = x 1 x + 1 f(x) = \frac{x-1}{x+1} and f n ( x ) f^{n}(x) denote the n fold n-\text{fold} composition of f f with itself. That is, f 1 ( x ) = f ( x ) f^1(x) =f(x) and f n ( x ) = f ( f n 1 ( x ) ) f^n(x) = f(f^{n-1}(x)) . Find f 2007 ( 2 ) f^{2007}(2) .


The answer is -3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Note that f 2 ( x ) = 1 x f^2(x) = -\frac{1}{x} f 3 ( x ) = x + 1 x 1 f^3(x) = -\frac{x+1}{x-1} f 4 ( x ) = x f^4(x) = x f 5 ( x ) = f ( x ) f^5(x) = f(x) Since the remainder r r when 2007 2007 is divided by 4 4 is 3 3 ( 2004 = 4 501 + 3 ) (2004 = 4*501+3) , it follows f 2007 ( x ) = f 3 ( x ) = x + 1 x 1 f^{2007}(x) = f^3(x) = -\frac{x+1}{x-1} .

Therefore, f 2007 ( 2 ) = 3 f^{2007}(2) = -3

Please don't post solutions, spare us the trouble of posting solutions. 😀

Hem Shailabh Sahu - 6 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...